Asbāb an-Nuzūl dalam Wacana Teologi Asy’ariyyah: - Heriyanto Heriyanto (SUHUF, 2017)
This paper discusses asbāb an-nuzūl (reasons of revelation) to be seen from the perspective of Ash’arite theology, particularly, al-Gazālī’s thought of the existence of asbāb an-nuzūl in the epistemology of Qur’anic interpretation. Once, Al-Gazālī had ever criticized the inevitability of causality, but on the other hand he also considered the Qur’an as an eternal one (qadīm). These two themes are used as an analytical framework to see the relation of al-Gazālī’s thought and the concept of asbāb an-nuzūl. The results of the study found that al-Gazālī in seeing the causal relationships existed in the asbāb al-nuzūl and the descending verses, Gazālī sees the importance of associative relationship (iqtirāniyyah), not implicative relationship (ta’ṡīriyyah). It means that al-Gazālī considers the relationship between the two is not a necessity or not necessarily affect one each other. The concept of asbāb an-nuzūl in al-Gazālī’s theology sees an event that causes the revelation of the verses is understood as an entity which God has chosen eternally. It is from this conception that in the epistemology of his interpretation, al-Gazālī considers the benefit of asbāb an-nuzūl study is informative only. He emphasizes more on the word spelling (lafaẓ) in general rather than the special cause in particular.